Exact Analytical Solutions for Modelling the Speed-Time Characteristics of Direct-Start Induction Machines under Various Operational Conditions on Ships: Review and Experimental Validation - Ilija Knezevic; Martin Calasan; Tatijana Dlabac; Filip Filipovic; Nebojsa Mitrovic (Elektronika ir Elektrotechnika)
Induction machines (IMs) are crucial to driving auxiliary machinery and devices of ships, such as pumps, fans, winches, and elevators, which are essential for maintaining the operational functions of a ship and are characterised by various types of loads. This is of critical importance because high surges of starting current can cause instabilities and fluctuations in a ship’s power system, directly affecting the safety and efficiency of ship operations. This paper provides a comprehensive review of analytical expressions for modelling the start-up time of directly started IMs under different ship operational conditions (no-load, linear load, fan load, and gravitational load). Validation of the analytical models was performed by comparing the speed-time characteristics obtained from the experimental measurements with the corresponding ones obtained by simulations in a MATLAB Simulink environment. The observed 1.5 kW IM reached a steady state for 0.1356 seconds when driving the load with a fan characteristic. However, when subjected to linear and gravitational loads, the IM requires longer times to reach a steady state - 0.1400 and 0.1606 seconds, respectively. The results of the simulations and experimental tests highly corresponded with the analytical predictions, confirming the reliability and practical applicability of the analytical models.